2019
DOI: 10.1007/s11676-019-01011-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of Abies spectabilis to climate along an elevation gradient of the Manang valley in the central Himalayas

Abstract: The Himalayas are characterized by a broad gradient of bioclimatic zones along their elevation. However, less is known how forest growth responds to climatic change along elevation. In this study, four standard treering width chronologies of Himalayan fir (Abies spectabilis) were developed, spanning 142-649 years along an elevation gradient of 3076-3900 m a.s.l. Principal component analysis classified the four chronologies into two groups; the ones at lower elevations (M1 and M2) and higher elevations (M3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 54 publications
(77 reference statements)
2
9
0
Order By: Relevance
“…Our results revealed that the radial growth of A. georgei was more affected by the moisture condition at a lower distributional range while by temperature at higher altitudinal sites in HSM, which supported one of our hypotheses that the strength of temperature impacts enhanced as altitude increased, but rejected another hypothesis that low temperature was the main factor controlling tree growth across the altitudinal distributional range. Consistent to our findings, the importance of moisture (temperature) decreased (increased) with increases in altitudes has been reported in nearby central Himalaya [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that the radial growth of A. georgei was more affected by the moisture condition at a lower distributional range while by temperature at higher altitudinal sites in HSM, which supported one of our hypotheses that the strength of temperature impacts enhanced as altitude increased, but rejected another hypothesis that low temperature was the main factor controlling tree growth across the altitudinal distributional range. Consistent to our findings, the importance of moisture (temperature) decreased (increased) with increases in altitudes has been reported in nearby central Himalaya [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we assessed seasonal and daytime differences in livestock depredation by snow leopards. Taking into account regional climatic conditions, we differentiated among depredation events in spring (March-May), summer (June-August), autumn (September-November), and winter (December-February; Department of Hydrology and Meteorology 2017; Rai et al 2020). We also differentiated between depredation events during daytime and night-time, when the time of the attack was known and did not fall into transition times (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of local climate data along the elevational gradient, we used the 30-arcsec gridded climatic database of Climatologies at High Resolution for the Earth's Land Surface Areas (CHELSA) from 1979 to 2013 (Karger et al, 2017). The reliability of the climatic data from CHELSA in the central Himalayas has been demonstrated by a recent study (Rai et al, 2020).…”
Section: Study Area and Climatementioning
confidence: 99%